Do Urbanization, Remittances, and Globalization Matter for Energy Consumption in Belt and Road Countries: Evidence From Renewable and Non-Renewable Energy Consumption - Zhao, Lijin; Qamruzzaman, Md. (Frontiers in Environmental Science, 2022)
Energy–growth nexus has gained immense interest among researchers, policymakers and academicians, and with conclusive evidence, it is revealed that sustainable economic growth significantly relies on energy availability and security. Another line of studies postulated that excessive fossil fuel application had created adversity for environmental degradation and ecological imbalance. Moreover, therefore, the transition of energy reliance has been happening from non-renewable sources to renewable sources. The motivation of the study is to explore the role of urbanization, remittances and globalization on energy consumption in BRI nations for the period 2004-2020. A panel of 59 (fifty-nine) BRI nations has considered as a sample countries' assessment and their selection purely depending on the data availability. Several panel data estimation techniques have been applied, including CIPS and CADF for panel unit root test, cointegration test with error correction, Dynamic Seemingly Unrelated Regression and causality test. The coefficient of globalization has exposed negative (positive) and statistically significant ties with non-renewable (renewable) energy consumption, whereas remittances and urbanization revealed positive and significant associations to both renewable and non-renewable energy consumption. The directional causality test documented bidirectional causality between globalization and renewable energy consumption and urbanization, globalization and remittances to non-renewable energy consumption,